Printability of Double Network Alginate-Based Hydrogel for 3D Bio-Printed Complex Structures - Greco, Immacolata; Miskovic, Vanja; Varon, Carolina; Marraffa, Chiara; Iorio, Carlo S. (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, 3D bioprinting has become a key technology in tissue engineering. In order to achieve high printing accuracy of complex structures it is crucial to understand how material selection and printer settings influence the outcome. For instance, hydrogels have been widely employed thanks to their biocompatibility, but their extrusion is of paramount importance to exploit their properties and achieve high shape fidelity. However, the printing settings are seldom addressed when printing hydrogels. In this context, this study explored the printability of hydrogels, from printing lines (1D structures) to lattices (2D structures) and 3D tubular structures, with a focus on printing accuracy. Critical correlations such as velocity and viscosity of the ink were identified after a series of tests. PEGDA/alginate-based double network hydrogels (DN) were explored and prepared, and printing conditions were improved to achieve 3D complex architectures, such as tubular structures. Because the DN solution ink was unsuitable for printability, glycerol was added to enhance the process. Different glycerol concentrations and flow rates were investigated. The solution containing 25% glycerol and a flow rate of 2mm/s yielded the best printing accuracy. Thanks to these parameters a line width of 1 mm and an angle printing inaccuracy of less than 1°, were achieved indicating good shape fidelity. Once the optimal parameters have been identified, we achieved the bioprinting of a tubular structure with high shape fidelity. Lastly, this study demonstrated a 3D printing hydrogel structure using a commercial 3D bioprinter (REGEMAT 3D BIO V1) by synchronizing all parameters, serving as a reference for future more complex 3D structures.